PENGARUH OPINI AUDITOR, GOOD CORPORATE GOVERNANCE DAN RETURN SAHAM TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR KEUANGAN YANG TERDAFTAR DI BEI - Shafwan Nur Rahmad Nasution; Tuti Meutia; Ainul Yusna Harahap (Jurnal Mahasiswa Akuntansi Samudra, 2023)
The purpose of this study was to determine the effect of auditor opinion, good corporate governance, and stock returns on financial performance. The approach used is quantitative, sample selection using purposive sampling technique from a total of 106 companies as a population, 13 companies in the financial sector were selected as research samples based on predetermined criteria. To analyze the data, multiple linear regression analysis was used. Data sources were obtained from secondary data from the Indonesia Stock Exchange and relevant research websites used as data sources, especially financial report data from 2012 to 2021. The findings of this study indicate that there is a significant influence of good corporate governance on financial performance. However, the auditor's opinion and stock returns were found to have no significant effect on financial performance, whereas simultaneously, auditor opinions, good corporate governance and stock returns had a significant effect on financial performance.